4-Amino-2-(p-tolyl)-7H-chromeno[5,6-d]oxazol-7-one - Evangelia-Eirini N. Vlachou; Thomas D. Balalas; Dimitra J. Hadjipavlou-Litina; Konstantinos E. Litinas (Molbank, 2021)
The new 4-amino-2-(p-tolyl)-7H-chromeno[5,6-d]oxazol-7-one was successfully prepared through the Au/TiO2-catalyzed NaBH4 activation and chemoselective reduction of the new 4-nitro-2-(p-tolyl)-7H-chromeno[5,6-d]oxazol-7-one. The latter was synthesized by the one-pot tandem reactions of 6-hydroxy-5,7-dinitrocoumarin with p-tolylmethanol under Au/TiO2 catalysis. The dinitrocoumarin was obtained by the nitration of 6-hydroxycoumarin with cerium ammonium nitrate (CAN). The structure of the synthesized compounds was confirmed by FT-IR, HR-MS, 1H-NMR and 13C-NMR analysis. Preliminary biological tests show low anti-lipid peroxidation activity for the title compound.